Promoting Pancasila values through dialectical project-based learning for Indonesian youth - Prihatin, Endang; Nurdin, Encep Syarief; Ruyadi, Yadi; Suhartati, Tri; Thabrani, An Nisaa Atila (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The young generation in Indonesia is confronted with specific challenges in navigating the adverse effects of globalisation, which have the potential to erode the values enshrined in Pancasila. This research project aims to investigate the efficacy of the Pancasila Dialectic Project model in the character formation of the younger generation, with a particular focus on the realisation of the values of Pancasila through innovative approaches. The methodology employed is a literature review, encompassing an examination of the theoretical foundations of the model and an analysis of empirical data derived from its implementation. The Pancasila Dialectic Project model employs a dialectic approach that engages the younger generation in open discussion through the use of a podcast format, which aligns with their digital lifestyle. The findings demonstrate that this model not only enhances comprehension of Pancasila but also fosters moral development through the cultivation of critical and collaborative dispositions. The results provide substantial evidence that a dialectical approach can be an efficacious strategy in fortifying the values of Pancasila among the younger generation, as well as promoting constructive discourse on national identity in the contemporary global context.